The Influence of the COVID-19 Pandemic on Physical Growth and Personal Hygiene of Adolescents - Halifu, Ruslan; Amiruddin, Ahmad; Samrida, Wa Ode Nesya J; Justin, Wa Ode Sitti; Sari, Selvi Mayang; Pabokori, Sudirman (UI Scholars Hub, 2023)
The COVID-19 pandemic has influenced the community's lifestyle, including adolescents’ behavior. One aspect majorly affected was physical growth, which encompasses several areas, including nutritional status and personal hygiene. Maintaining the quality of physical growth is very important, even beyond the pandemic. Therefore, this study aimed to determine the influence of the COVID-19 pandemic on adolescents' nutritional status and personal hygiene. A literature review method was used through a bibliometric and content analysis of publications obtained from databases such as Google Scholar. The articles obtained were classified by publication year, study location, keywords, and journal titles. Based on the literature search, 11 articles were found on the influence of the COVID-19 pandemic on the nutritional status of adolescents, and 10 articles discussed the effect on personal hygiene. After reviewing the articles, it was concluded that the pandemic influenced adolescents' nutritional status and personal hygiene.